Cyclodextrin A Versatile Ingredient - Arora, Poonam; Dhingra, Neelima (IntechOpen, 2018)
The book is devoted to the highly versatile and potential ingredient Cyclodextrin, a family of cyclic oligosaccharides composed of ?-(1,4)-linked glucopyranose subunits. Its molecular complexation phenomena and negligible cytotoxic effects attribute toward its application such as in pharmaceuticals, cosmetics, food, agriculture, textile, separation process, analytical methods, catalysis, environment protection, and diagnostics. Efforts have also been made to concentrate on recent research outcomes along with future prospects of cyclodextrins to attract the interest of scientists from the industry and academia. The contributions of the authors are greatly acknowledged, without which this compilation would not have been possible.